Theoretical and Practical Advances in Computer-based Educational Measurement - Veldkamp, Bernard P.; Sluijter, Cor (Methodology of Educational Measurement and Assessment,, 2019)
This open access book presents a multitude of different, yet related, innovations in educational measurement and provides insight in their practical possibilities. The book not only addresses several improvements in the quality of educational measurement and innovations in (inter)national large scale assessments, but also several advances in psychometrics and improvements in computerized adaptive testing. Moreover, it also offers examples on the impact of new technology in assessment. By bringing together expertise from this variety of fields, advances in assessment are fostered and stimulated. A wide range of topics by authors from both an academic and a professional background are discussed, among which are review systems tailored for the evaluation of the quality of computer-based educational tests, the Curie-Weiss model as a paradigm for the analysis of educational data, Bayesian techniques to decide on mastery in formative educational measurement and the comparisonof Elo chess ratings as strategies for on-the-fly item calibration in computerized adaptive tests. Due to its nature, the book appeals to a broad audience within the educational measurement community. As well as helping to expand theoretical knowledge, it also provides examples of practical implementation of innovations in testing technology and educational measurement.